Assessing two methods for agrochemical application (Tractor-Based and UAV) in rice fields - Arroyo-Mejías, Esteban (2024)
Introduction. Rice is one of the world’s most consumed grains in the world and is the most cultivated annual crop in Costa Rica. During rice’s growth, some kernel characteristics can be enhanced by using plant growth regulators (PGR), usually sprayed over the crop with a tractor-based spray boom (SB). Recently, the use of Unmanned aerial vehicle (UAV) sprayers, in PGR applications, has become more common. However, the lack of efficiency compared with conventional methods (as SB) urges research development. Objective. To compare spraying efficiency of SB and UAV using a PGR over rice (Oryza sativa). Materials and methods. Three treatments of different volumes with SB (SB100=100 L ha-1, SB150=150 L ha-1 and SB200=200 L ha-1), three treatments with UAV (D10=10 L ha-1, D20=20 L ha-1 and D30=30 L ha-1) and one control (no spray application) were conducted in a rice field located in Pavones, Guanacaste, Costa Rica. Five repetitions were carried out in a completely randomized design for all treatments with different PGR rates and considering spraying quality (coverage, uniformity and droplet density), rice yield, and rice milling quality as efficiency parameters. Results and discussion. SB and UAV treatments did not present statistical differences in rice milling quality and yield. Considering the spray quality for SB, SB100 complied with the required droplet density (more than 20 drops cm-2), while being the treatment with the lowest water use. As for spray quality in UAV treatments, neither had the minimum droplet density required (7.44 - 17.4 drops cm-2), in addition to a poor uniformity performance with high values of coefficient of variation (48.49 - 57.77%). Conclusion. After evaluating the efficiencies of SB and UAV treatments, SB100 is the most efficient method based only on the spray quality parameter, since rice milling quality and yield did not present statistical differences.